Pengaruh Kepemimpinan, Motivasi dan Disiplin Kerja terhadap Kepuasan Kerja Guru di SMP Negeri 17 Balikpapan Utara - Tamzil Yusuf; ImamArrywibowo; Wulan Agustina Rusady (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Teacher Job Satisfaction has a crucial role in improving the quality of education in schools, and internal factors such as effective leadership, high motivation and good work discipline have been identified as important elements in creating a conducive work environment. This research aims to explore the extent to which leadership, motivation and work discipline influence the level of teacher job satisfaction at SMP Negeri 17 North Balikpapan. By identifying the relationship between these variables, this research also aims to provide relevant recommendations for the development of human resource management policies in these schools. The research uses a quantitative approach with data collection methods through questionnaires. The sample consisted of 35 teachers at SMP Negeri 17 North Balikpapan, who were selected using non-probability techniques. The collected data is analyzed using statistical techniques such as regression to test the proposed hypotheses. The software used in this research uses smartPls. The research results show that leadership has a positive but not significant influence on teacher job satisfaction. Motivation is proven to have a positive and significant influence on job satisfaction, while work discipline also has a positive influence on teacher job satisfaction. These findings provide a deeper understanding of the factors that influence teacher job satisfaction at SMP Negeri 17 North Balikpapan, as well as practical implications for the development of human resource management in schools.